Localized Acquired Hypertrichosis Associated with the Application of a Splint - Alexander K. C. Leung; Andrew S. Wong (Case Reports in Pediatrics)
We describe a 16-year-old boy whose left forearm and hand were cut by a piece of glass from a broken window as a result of the fall. He had surgical repair of his left extensor pollicis brevis, abductor pollicis brevis, and dorsal branch of the left radial nerve. Following the surgery, he was put on a splint so as to immobilize the left forearm and wrist. On removal of the splint 4 weeks post surgery, he was noticed to have more hair growth on his left forearm and hand than his right counterparts. The patient was reassessed 2, 4, and 8 months after the removal of the splint. The hypertrichosis got better with time. At the last visit, the hair growth in the left forearm and hand was back to normal. Our patient represents the first reported case of localized acquired hypertrichosis following the application of a splint in the pediatric literature.